2016
DOI: 10.1164/rccm.201601-0108oc
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Effects of Reward- and Deposit-based Financial Incentives on Smoking Cessation

Abstract: Rationale: Targeting different smoking cessation programs to smokers most likely to quit when using them could reduce the burden of lung disease.Objectives: To identify smokers most likely to quit using pure reward-based financial incentives or incentive programs requiring refundable deposits to become eligible for rewards.Methods: We conducted prespecified secondary analyses of a randomized trial in which 2,538 smokers were assigned to an $800 reward contingent on sustained abstinence from smoking, a refundab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Our findings in Table 2 indicating that male employees were significantly less likely to participate confirm the findings of several large meta-analyses of workplace preventive programs and workplace smoking cessation programs [3][4][5][6] . In a meta-regression of 23 worksite prevention programs, Robroek et al 5 found that women had significantly higher participation than men (OR=1.67; 95% CI: 1.25-2.27), but that this advantage was not apparent for preventive programs on physical fitness (i.e.…”
Section: Participant Demographic and Health Factorssupporting
confidence: 88%
See 4 more Smart Citations
“…Our findings in Table 2 indicating that male employees were significantly less likely to participate confirm the findings of several large meta-analyses of workplace preventive programs and workplace smoking cessation programs [3][4][5][6] . In a meta-regression of 23 worksite prevention programs, Robroek et al 5 found that women had significantly higher participation than men (OR=1.67; 95% CI: 1.25-2.27), but that this advantage was not apparent for preventive programs on physical fitness (i.e.…”
Section: Participant Demographic and Health Factorssupporting
confidence: 88%
“…One factor contributing to the high participation rate in the LLUH BREATHE cohort in smoking cessation was the use of an individual 'reward-based' incentive (as opposed to 'deposit-based' incentive) -a method that has been shown in two large systematic reviews 3,5 and one large randomized controlled trial 6,7 to be very effective in accomplishing both participation and higher rates of smoking cessation 10,12 . LLUH BREATHE participants promoted smoking cessation by enrolling in the health plan that contained reduced monthly out-of-pocket contribution, prescription drug costs and co-payments -thus tangibly increasing their individual monthly income.…”
Section: Encouraging Successful Smoking Cessationmentioning
confidence: 99%
See 3 more Smart Citations